Forensic mental health : framing integrated solutions - Bratina, Michele P. (Routledge, 2017)
"Forensic Mental Health : Framing Integrated Solutions describes a criminal justice-mental health nexus that touches every population--juvenile and adult male and female offenders, probationers and parolees, the aging adult prison population, and victims of crime. In the US today, the criminal justice system functions as a mental health provider, but at great cost to society. The author summarizes the historical roots of this crisis and provides an overview of mental illness and symptoms, using graphics to illustrate the most prevalent disorders encountered by police and other first responders. Bratina demonstrates in detail how the Sequential Intercept Model (SIM) supports integration of the US healthcare and justice systems to offer more positive outcomes for offenders with mental illness."--